Analysis of China's energy consumption changing using the Mean Rate of Change Index and the logarithmic mean divisia index. (15th January 2019) - Wang, Yanqiu; Zhu, Zhiwei; Zhu, Zhaoge; Liu, Zhenbin
Abstract: The principle of input-output analysis, the Mean Rate of Change Index and the Logarithmic Mean Divisia Index were used to conduct the quantitative analysis of the current China's energy consumption from the national industrial level and regional level. It was aimed to calculate the impact and contribution rate of various factors on energy consumption growth in China. The purpose of this research is to analyze the changes of energy consumption of the 30 provinces in China during the period of 2006–2015. The results show that the output scale effect and production structure effect play a leading role in China's energy consumption growth, while China's energy intensity effect can effectively suppress it. The scale effect of output and the energy intensity effect are the main driving factors affecting the growth of China energy consumption. The scale effect of output plays a promoting role of the growth of China energy consumption, and the energy intensity effect can effectively curb the growth of China energy consumption. Highlights: Decomposition method for energy-consumption analysis is applicable. The scale effect of output has a positive impact on the growth of energy consumption. Energy intensity effect has a negative impact on the growth of energy consumption. Production structure effect make China's energy consumption continue to grow.